Republic of Lithuania : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix analyzes economic developments in Lithuania during 1996-99. The paper discusses macroeconomic developments and policies in detail. It discusses the importance of fiscal prudence in maintaining sustainable fiscal and external positions over the medium term, and emphasizes that reining in budgetary spending will be a key challenge in the period ahead. The paper reviews external competitiveness and concludes that Lithuania's competitiveness has remained adequate through early 1999, although there remains little room for further real appreciation and wage rises that are not related to productivity increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet